Office workers and video display terminals: physical, psychological and ergonomic factors. - Travers PH; Stanton B (AAOHN Journal, 2002)
The purpose of the pilot study was to examine the psychological and physical symptoms reported by video display terminal (VDT) and non-VDT users in relation to intensity and duration of VDT exposure, ergonomic characteristics of the work station, workers' perceptions of the working environments, medical conditions, job satisfaction, and mood states. Thirty VDT users and 16 non VDT users were selected from four departments of a major radiopharmaceutical company for participation in the cross-sectional study. Self-administered questionnaires were utilized to obtain information on symptoms, medical conditions, job satisfaction, mood states, and the working environments. Objective measurements were obtained to provide information on the various ergonomic components of the work station. The study corroborated findings reported in previous studies, whereby eye related symptoms were associated with VDT usage. A higher percentage of symptoms were reported among VDT users even when they had more control over their work stations. These workers expressed higher levels of job satisfaction, and lower levels of tension, fatigue, confusion, anger, and depression than non-VDT users. Most importantly, a trend in symptomatology was identified, whereby symptoms appeared to increase as duration of VDT exposure increased.